PENGARUH BUKU ANAK CERITA ISLAMI TERHADAP KECERDASAN SPIRITUAL ANAK USIA USIA 5-6 RA WADAS KELIR PURWOKERTO SELATAN - Hafidz, Nur; Arfina, Desi; Nurbaiti, Amalia (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Agama Islam Universitas Nahdlatul Ulama Purwokerto, 2023)
Spiritual intelligence is the intelligence of each individual related to behavior or attitude actions. Spiritual intelligence must be instilled from an early age. Considering this spiritual intelligence, it is important that there is one medium to hone children's spiritual intelligence, namely with the media of Islamic children's story books, by presenting stories of the prophet, stories of friends, and exemplary values for early childhood. Islamic children's story books have the characteristics of simple language with concepts with 2-4 sentences, attractive illustrations, and easy to reflect. Thus, Islamic children's story books aim to find out the influence of Islamic children's story books on the spiritual intelligence of children aged 5-6 years in Raudhatul Athfal Wadas Kelir Purwokerto Selatan. This type of research uses quantitative data analysis with simple regression, using the SPSS 25 application to draw conclusions. Based on the results of this research, there is a significant influence of Islamic children's story books on the spiritual intelligence of children aged 5-6 years in Raudhatul Athfal Wadas Kelir Purwokerto Selatan. The resulting data obtained a calculated value of 9,450, while t table with N = 20, a significance level of 0.05 is 1,910, meaning tcount > tcount. It can be concluded that Ho is rejected and Ha is accepted. The results of the simple linear regression equation, namely Y = 11, 264+ 860 X, are positive. The contribution of Islamic children's story books to the spiritual intelligence of early childhood is 83.2% and 16.8% is influenced by other factors.